2012
DOI: 10.1371/journal.ppat.1002712
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Ifit2/ISG54 Protects Mice from Lethal VSV Neuropathogenesis

Abstract: Interferon protects mice from vesicular stomatitis virus (VSV) infection and pathogenesis; however, it is not known which of the numerous interferon-stimulated genes (ISG) mediate the antiviral effect. A prominent family of ISGs is the interferon-induced with tetratricopeptide repeats (Ifit) genes comprising three members in mice, Ifit1/ISG56, Ifit2/ISG54 and Ifit3/ISG49. Intranasal infection with a low dose of VSV is not lethal to wild-type mice and all three Ifit genes are induced in the central nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
183
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(191 citation statements)
references
References 43 publications
(64 reference statements)
7
183
1
Order By: Relevance
“…ISG58 expression can be induced strongly upon viral infection [4], therefore, we sought to examine the potential inhibitory effect of ISG58 on viral replication by using a model of vesicular stomatitis virus expressing GFP (VSV-GFP). Earlier work reported that both ISG54 and ISG56 inhibited VSV replication when they were overexpressed in HEK293T cells [1,7]. Similarly, ISG58 reduced VSV replication by more than 60% ( Figure 1G).…”
Section: Dear Editormentioning
confidence: 55%
“…ISG58 expression can be induced strongly upon viral infection [4], therefore, we sought to examine the potential inhibitory effect of ISG58 on viral replication by using a model of vesicular stomatitis virus expressing GFP (VSV-GFP). Earlier work reported that both ISG54 and ISG56 inhibited VSV replication when they were overexpressed in HEK293T cells [1,7]. Similarly, ISG58 reduced VSV replication by more than 60% ( Figure 1G).…”
Section: Dear Editormentioning
confidence: 55%
“…Previous studies have demonstrated that viral infection can stimulate expression of ISGs and proinflammatory cytokines in cultured CNS cells and in the brain (8,10,55,56) and that both neurons and glia are responsive to IFN treatment (57)(58)(59). Additionally, studies tracking virus spread into the brain from peripheral sites of inoculation have highlighted the importance of the innate immune response in preventing high virus load within the brain (14,50,60,61). However, there have been no studies that resolved whether an innate immune response mounted within the brain parenchyma can limit viral spread, especially along neuronal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Although type I IFN is essential for the protection of hosts from lethal infection with a variety of RNA viruses, such as influenza A virus (IAV) and vesicular stomatitis virus (VSV), type I IFN is not essential for induction of the antiviral state against MLV (16)(17)(18). Therefore, a different type of innate immune system has been proposed to protect hosts from MLV infection.…”
mentioning
confidence: 99%